Rendemen dan Skrining Fitokimia pada Ekstrak Daun Sanseviera sp. - Dewatisari, Whika Febria; Rumiyanti, Leni; Rakhmawati, Ismi (Politeknik Negeri Lampung., 2017)
The aims of this research was determined from yield analysis on the leaves extract of Sansevieria trifasciata and Sansevieria cylindrica. It was also determined by the presence of bioactive compounds that have the potential as antioxidants (phytochemical screening) on the leaves extract of S. trifasciata and S. cylindrica.The method used was a stratified extraction method with three types of solvent, ie non-polar solvent in the form of N Hexan; A semi-polar solvent of Aceton; And a polar solvent of Ethanol. The identification of six types of phytochemical compounds, the triterpenoid and steroid compounds, saponins, phenols, flavonoids, quinones and alkaloids. The result of rendement analysis showed that S. trifasciata yield was higher than S. cylindrica. The yield of S. trifasciata was 7.89 % and S. cylindrica 6.79%. The result of phytochemical compound analysis obtained three phytochemical compounds contained in S. trifasciata, named triterpenoid group compounds and steroids and flavonoids. Meanwhile, the results of the analysis of phytochemical compounds contained in S. cylindrica also obtained three phytochemical compounds, namely triterpenoid compounds and steroidal groups and alkaloids.